The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/joic.12188
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Amplatzer Vascular Plug II Device to Occlude Different Types of Patent Ductus Arteriosus in Pediatric Patients

Abstract: The AVP II is an effective and safe device for PDA closure. It is particularly useful when dealing with nontypical PDA shapes and in small infants where it eliminated the risk of device-related aortic obstruction. The AVPII is an addition to the PDA device closure armamentarium in pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 28 publications
4
33
2
2
Order By: Relevance
“…The incidence of LPA stenosis with AVP II (19/421) was higher when compared to data published by Garay et al, who noted LPA stenosis in 1/294 cases. Their rate of device embolization in 4/294 cases (1.4%) is similar to our series 5/421 (1.2%).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The incidence of LPA stenosis with AVP II (19/421) was higher when compared to data published by Garay et al, who noted LPA stenosis in 1/294 cases. Their rate of device embolization in 4/294 cases (1.4%) is similar to our series 5/421 (1.2%).…”
Section: Discussioncontrasting
confidence: 57%
“…To reduce the risks of device embolization, left pulmonary artery (LPA) stenosis and coarctation of the aorta (CoA) seen with the use of approved devices, the interventionalists have been using Amplatzer Vascular Plugs (AVP) I, II, and IV, muscular VSD devices, ASD devices, and microvascular plugs …”
Section: Introductionmentioning
confidence: 99%
“…The ADO IV has also been utilized and shares this flexibility . Garay et al reported a large, multicenter trial of PDA closure with the AVPII . While the majority of PDAs were closed with minimal complications, one disc is deployed in the pulmonary artery ampulla, resulting in possible LPA stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, size of the delivery systems as well as risk of aortic and/or left pulmonary artery obstruction secondary to device implantation makes this option still challenging in small neonates and infants . To overcome these drawbacks, modified devices as the Amplatzer Vascular Plug and the Amplatzer Duct Occluder type II were engineered by the AGA Medical Corporation, the more pliable and trackable of which is the Amplatzer ® Duct Occluder (ADO) II device that may be deployed by 4Fr delivery catheters . However, its occluding discs are still too large to nicely accommodate into small pulmonary artery and aortic isthmus.…”
Section: Discussionmentioning
confidence: 99%